Risk of livedo with antiphospholipid antibodies in patients with systemic lupus erythematosus: A systematic review and meta-analysis. (November 2022) - Loiseau, Pierre; Foret, Thomas; DeFilippis, Ersilia M; Risse, Jessie; Etienne, Anais D; Dufrost, Virginie; Moulinet, Thomas; Erkan, Doruk; Devilliers, Hervé; Wahl, Denis; Zuily, Stéphane
Background: Livedo is a well-known skin condition in patients with systemic lupus erythematosus (SLE) which correspond to small vessels involvement. The influence of antiphospholipid antibodies (aPL) on the occurrence of livedo is controversial. The aim of our study was to estimate the risk of livedo associated with aPL in patients with SLE. Methods: We conducted a systematic review and meta-analysis of the literature from 1977 to 2021 to estimate the risk of livedo in SLE patients according to different aPL profiles. Data sources were PubMed, Embase, Cochrane Library, hand search, and reference lists of studies. Studies were selected if they included SLE patients with descriptions of the exposure to aPL and the outcome ( livedo ). Two independent investigators assessed study eligibility, quality, and extracted patient characteristics from each study as well as exposure (aPL) and outcome ( livedo ). Risk estimates were pooled using random effects models and sensitivity analyses. For all stages of the meta-analysis, we followed the PRISMA guidelines. PROSPERO registration number: CRD42015027377. Results: Of the 2, 355 articles identified, 27 were included with a total of 4, 810 SLE patients. The frequency of livedo was 25.5% in aPL-positive patients and 13.3% in aPL-negative patients. The overall Odds Ratio (OR) for livedo in aPL-positive patients compared to aPL-negative patients was 2.91 (95% CI; 2.17–3.90). The risk of livedo was significantly increased for most of aPL subtypes, including lupus anticoagulant (LA) (OR = 4.45 [95% CI; 2.21–8.94]), IgG anticardiolipin (OR = 3.95 [95% CI; 2.34–6.65]), and IgG anti-β2 -glycoprotein 1 (OR = 3.49 [95% CI; 1.68–7.27]). Conclusions: We demonstrated in this meta-analysis an excess risk of livedo in aPL-positive SLE patients compared to aPL-negative patients. For daily practice, in patients with SLE, livedo associated with aPL could correspond to a peculiar group of patients with small vessel disease. Livedo could be a good candidate for inclusion in future classification criteria for antiphospholipid syndrome.